Balancing emotional processing with ongoing cognitive activity: the effects of task modality on intrusions and rumination - Curci, Antonietta; Soleti, Emanuela; Lanciano, Tiziana; Doria, Valentina; Rimé, Bernard (Frontiers in Psychology, 2015)
In the present paper we aimed to show that competition for resources between post-emotional processes and the execution of a cognitive task will result in two possible effects: (1) an impairment of the cognitive task in the short run and (2) an elongation of intrusions and rumination in the long run. The outcome of this competition is influenced by the interaction of the modality (verbal vs. visuospatial) of cognitive tasks run in the aftermath of an emotional experience and the nature (verbal vs. visuospatial) of the same experience. Nonclinical participants were given a Working Memory task (OSPAN vs. an analogue Visual task) before and after the presentation of negative vs. neutral material (a novel excerpt in Experiment 1 and a video clip in Experiment 2). Intrusions and rumination were measured after a 24-hour delay. Rumination was also assessed immediately after the experimental induction. Results showed that exposure to verbal negative material impaired verbal performance (Experiment 1); by contrast, exposure to visual negative material impaired both verbal and visuospatial performance (Experiment 2). Intrusions were only affected by the emotional valence of the original experience, while performing a visuospatial task resulted in enhanced rumination only after exposure to verbal emotional material. The findings of both experiments suggest that emotional processing spreads over time in balance with ongoing cognitive activities, and, in such a balance, the visuospatial processing mode tends to prevail over verbal engagements.